2002
DOI: 10.1192/bjp.181.5.433
|View full text |Cite
|
Sign up to set email alerts
|

Survivors of the Piper Alpha oil platform disaster: long-term follow-up study

Abstract: Evidence from neuroimaging studies has suggested areas of the brain that may be damaged by psychological trauma. The clinical implications of these neuroimaging findings need to be investigated further because they challenge traditional therapeutic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
1
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(110 citation statements)
references
References 20 publications
4
102
1
3
Order By: Relevance
“…In comparison, for the non-bereaved participants, there were 10/113 (8.8%) who developed PTSD, which underscores bereavement as a risk factor for long-term PTSD (Arnberg et al, 2011). Further, our prevalence rates were lower than in studies of directly exposed victims from both natural and anthropogenic disasters (Bøe et al, 2011;Favaro, Zaetta, Colombo, & Santonastaso, 2004;Hull et al, 2002;North, Pfefferbaum, et al, 2011;North, Pollio, et al, 2011). This study concerned an event very remote to the homes of the survivors and that the beliefs common in people with PTSD about the world as dangerous (e.g., no place is safe) may have been easier to reevaluate by the survivors in their processing of the event, as compared to the more plausible (and realistic) negative beliefs about the world if the index trauma took place in or close to the survivors' homes.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In comparison, for the non-bereaved participants, there were 10/113 (8.8%) who developed PTSD, which underscores bereavement as a risk factor for long-term PTSD (Arnberg et al, 2011). Further, our prevalence rates were lower than in studies of directly exposed victims from both natural and anthropogenic disasters (Bøe et al, 2011;Favaro, Zaetta, Colombo, & Santonastaso, 2004;Hull et al, 2002;North, Pfefferbaum, et al, 2011;North, Pollio, et al, 2011). This study concerned an event very remote to the homes of the survivors and that the beliefs common in people with PTSD about the world as dangerous (e.g., no place is safe) may have been easier to reevaluate by the survivors in their processing of the event, as compared to the more plausible (and realistic) negative beliefs about the world if the index trauma took place in or close to the survivors' homes.…”
Section: Discussionmentioning
confidence: 54%
“…Numerous studies have assessed the incidence and prevalence of posttraumatic stress disorder (PTSD; American Psychiatric Association, 2000) after disasters (Neria, Nandi, & Galea, 2008), which is a disabling disorder related to high rates of comorbidity and suicidal ideation (Cougle, Resnick, & Kilpatrick, 2009). Yet, despite consistent findings that PTSD is unlikely to remit if persisting beyond 6 years (Green, Lindy, Grace, & Leonard, 1992;Hull, Alexander, & Klein, 2002;North, Oliver, & Pandya, 2012), the overwhelming majority of studies have been conducted within the first 2 years postdisaster (Norris, 2006). Further, extant studies of long-term PTSD concern events that entailed severe secondary and collateral stressors that may exacerbate or prolong the prevalence rates of PTSD (Arnberg, Eriksson, Hultman, & Lundin, 2011;Brewin, Andrews, & Valentine, 2000): For example, substantial loss of property or possessions (Green et al, 1992), prolonged anxiety and fear because of terrorist attacks (North, Pfefferbaum, Kawasaki, Lee, & Spitznagel, 2011), and unemployment (Bøe, Holgersen, & Holen, 2011;Hull et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of long-term psychological and occupational support for burn disaster survivors was emphasized by Hull et al, who recently reported 10- year follow-up data on 33 of 59 survivors of the 1988 Piper Alpha oil rig fire (11). Twenty-two percent of the 33 subjects met criteria for post-traumatic stress disorder (PTSD) at the time of the study, and 73% retrospectively met criteria for PTSD during the first 3 months after the disaster.…”
Section: Performing Organization Name(s) and Address(es)mentioning
confidence: 99%
“…Twenty-two percent of the 33 subjects met criteria for post-traumatic stress disorder (PTSD) at the time of the study, and 73% retrospectively met criteria for PTSD during the first 3 months after the disaster. The majority (78%) reported difficulties finding work (11). The Bashkirian train-gas pipeline disaster of 1989 in the former Soviet Union provided an example of effective non-wartime international cooperation in the management of a burn mass casualty disaster (12).…”
Section: Performing Organization Name(s) and Address(es)mentioning
confidence: 99%
See 1 more Smart Citation